2009
DOI: 10.1542/neo.10-10-e502
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Crying Facies

Abstract: Drs Shapira and Borochowitz have disclosed no financial relationships relevant to this article. This commentary does not contain a discussion of an unapproved/ investigative use of a commercial product/ device. Objectives After completing this article, readers should be able to: 1. Know the causes of asymmetric crying facies (ACF). 2. Differentiate ACF from true facial paralysis. 3. Recognize the malformations that might be associated with ACF. 4. Evaluate an infant who has ACF. AbstractAsymmetric crying facie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…[ 4 , 7 ] Familial occurrence has been reported, and the mode of inheritance has been suggested as autosomal dominant inheritance with variable expressivity. [ 8 , 9 ] Some studies revealed that it is associated with chromosomal anomalies, such as 22q11.2 deletion. [ 10 , 11 ] Therefore, genetic deletion testing should be suggested when ACF is suspected in a newborn.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 7 ] Familial occurrence has been reported, and the mode of inheritance has been suggested as autosomal dominant inheritance with variable expressivity. [ 8 , 9 ] Some studies revealed that it is associated with chromosomal anomalies, such as 22q11.2 deletion. [ 10 , 11 ] Therefore, genetic deletion testing should be suggested when ACF is suspected in a newborn.…”
Section: Discussionmentioning
confidence: 99%
“…The ACF neonates show both nasolabial folds with normal, symmetrical depth and do have the normal ability to lift their forehead and close both eyes. This anomaly must be distinguished from facial nerve paralysis, which is less common [5]. In 20-70% of cases, ACF is associated with other congenital abnormalities, the most common being head/neck, cardiovascular, musculoskeletal, genitourinary and gastrointestinal.…”
Section: Incidencementioning
confidence: 99%
“…Asymmetric crying facies (ACF) is characterised by lower lip asymmetry in neonates only during crying 1. ACF has an incidence of 1:160 live births 1.…”
Section: Descriptionmentioning
confidence: 99%
“…ACF has an incidence of 1:160 live births 1. It can result from a developmental abnormality caused by absence (agenesis) or incomplete development (hypoplasia) of the depressor muscle of the angle of the mouth or of the depressor muscle of the lower lip; likewise, it can result from a traumatic compression of the facial nerve in utero or during labour 1 2…”
Section: Descriptionmentioning
confidence: 99%